The Importance of a Learner Management System in Implementing Data-driven Instruction in Higher Education Institutions (Journal of the Digital Humanities Association of Southern Africa, 2024)
The Covid-19 pandemic has resulted in the worst downturn in the global economy since the Great Depression in the 1930s. To face the challenges of the global economy, a person needs to possess basic skills including educational skills. Education plays a vital role in building a competitive economy that will hardly be affected by crisis and will be able to ensure that there are high rates of social development. The student population has become very diverse over the decades, making it difficult to teach. Teaching has become very complex to handle because of the increase in a variety of teaching strategies and the diverse student population. There is therefore a need for inclusive and equity pedagogy where teaching considers the diversity of students and the need for teachers to develop teaching strategies that support all students, especially those from disadvantaged backgrounds. The most expensive education is the one that is not completed. This conceptual paper looks at the importance of the Learner Management System (LMS) in implementing data-driven instruction to achieve quality education for all types of students. The LMS is a software system that tracks students’ participation and progress through data systems and assessments. It’s a platform that stimulates an environment for learner achievement and engagement. ‘Data-driven instruction’ can be defined as using student data to enhance instructional practices in the classroom to address the needs and learning styles of individual students. Additionally, data-driven instruction will be explored to discover how it can be used as a systematic and purposeful work to maximise the students’ performance. The study will provide recommendations on how LMS and data-driven instruction can be used to give direction to decisions to improve the students' outcomes.
Keywords: Data-driven instruction; Instruction; Learner Management System